La production éditoriale à Jumièges vers le milieu du Xe siècle - Jacques Le Maho (Tabularia)
The monastery of Jumièges was restored in 942 by duke William Longsword. Upon his death, king Louis IV d’Outremer having assumed the regency of the duchy, the abbey had to face the hostility of royal deputies. It is probably during this period that four texts were written with the purpose of supporting the interests of Jumièges: the Life of saint Aycadre, the Life of saint Hugh, a Life of William Longsword (now lost) and the famous Lament for the death of the late duke. In the present state of knowledge, these four literary works could be the earliest written records in Normandy after 911.